Effectiveness of interventions to improve adherence to antidepressant medication in patients with depressive disorders: a cluster randomized controlled trial - del Pino-Sedeño, Tasmania; González-Pacheco, Himar; González de León, Beatriz; Serrano-Pérez, Pedro; Acosta Artiles, Francisco Javier; Valcarcel-Nazco, Cristina; Hurtado-Navarro, Isabel; Rodríguez Álvarez, Cristobalina; Trujillo-Martín, María M.; , on behalf of MAPDep Team (Frontiers in Public Health, 2024)
Aim To assess the effectiveness of two interventions of knowledge transfer and behavior modification to improve medication adherence in patients with depressive disorders. Methods An open, multicenter, three-arm clinical trial with random allocation by cluster to usual care or to one of the two interventions. The intervention for psychiatrists (PsI) included an educational program based on a patient-centered care model. The intervention for patients and relatives (PtI) included a collaborative care program plus a reminder system that works using an already available medication reminder application. The primary outcome was patient adherence to antidepressant treatment assessed through the Sidorkiewicz Adherence Instrument. Secondary measures were depression severity, comorbid anxiety and health-related quality of life. Mixed regression models with repeated measures were used for data analysis. Results Ten psychiatrists and 150 patients diagnosed with depressive disorder from eight Community Mental Health Units in the Canary Islands (Spain) were included. Compared with usual care, no differences in long-term adherence were observed in either group PsI or PtI. The PsI group had significantly improved depression symptoms (B = −0.39; 95%CI: −0.65, −0.12; p = 0.004) during the follow-up period. The PtI group presented improved depression symptoms (B = −0.63; 95%CI: −0.96, −0.30; p < 0.001) and mental quality of life (B = 0.08; 95%CI: 0.004, 0.15; p = 0.039) during the follow-up period. Conclusion The assessed interventions to improve adherence in patients with depressive disorder were effective for depression symptoms and mental quality of life, even over the long term. However, no effect on antidepressant adherence was observed.